Performance evaluation of geospatially assisted reference evapotranspiration models - Pandi, Dinagarapandi; Saravanan, Kothadaramanan; Kuppusamy, Mohan; Birasnav, M. (Arabian Journal of Geosciences, 2022)
Mapping of spatiotemporal distribution of evapotranspiration becomes important for sustainable water management as water scarcity is nowadays a growing concern in almost all the continents. In general, researchers estimate evapotranspiration by multiplying the computed reference evapotranspiration (ETo) with the corresponding crop coefficient. Such estimation of ETo requires data related to spatiotemporal meteorological and vegetation field characteristics, and however, these data are rarely available in most developing countries such as India. Thus, researchers constantly develop various methods and evaluate the applicability of these methods to accurately capture spatiotemporal distribution. The purposes of this study are to (a) examine the applicability of Hargreaves and MODIS ETo method to map the spatiotemporal distribution over Thamirabarani basin located in Southern India and (b) evaluate the performances of Hargreaves and MODIS ETo methods and compare it to FAO 56 Penman–Monteith method. To achieve these purposes, ETo data of Hargreaves method and MODIS ETo method over Cheranmadevi meteorological observatory are extracted and performances of these methods are compared with FAO 56 Penman–Monteith method. Results show that a match exists among all the three ETo datasets, and no major deviations have been observed. However, this study suggests local calibration of Hargreaves and MODIS ETo method as considerable mismatch has been observed at ETo daily value. Overall, the conclusion of this study encourages the application of the Hargreaves method and MODIS ETo method in developing countries, where the data shortage condition prevails.
Keywords: Evapotranspiration; FAO 56 Penman–Monteith method; Hargreaves method; MODIS ETo; Thamirabarani basin; dept.mgt; peer-reviewed

Total quality leadership and organizational innovativeness: the role of social capital development in American schools - Birasnav, M.; Gantasala, Swapna Bhargavi; Gantasala, Venugopal Prabhakar; Singh, Abhishek (Benchmarking: An International Journal, 2022)
Purpose The purpose of this study is to explore the relationship between total quality leadership, social capital development and organizational innovativeness in the school environment. While there are research studies focused on the impact of leadership on implementing quality management practices, innovation and organizational performance, the mediating effect of social capital development has not been explored on the influence of the school leaders. Design/methodology/approach To achieve the purpose of this study, data collected from 158 principals, who participated in the Teaching and Learning International Survey 2018, were analyzed using structural equation modeling. Findings This study found that total quality learning-oriented school leaders are supportive of developing social capital in their schools, and such social capital development is very useful to improve organizational innovativeness. Interestingly, social capital development has been found to mediate the relationship between total quality learning-oriented school leadership and organizational innovativeness. Practical implications This study submits evidence for two major activities that school leaders perform: learning- and control-oriented activities, both being important for improving and measuring quality in the educational sector. This study clearly shows that control-oriented activities lean toward negatively on social capital while learning-oriented activities strongly and positively influence social capital development. From this study, practitioners can be aware and consciously promote social capital development in schools and that social capital development mediates the influence of total quality leadership and innovation in schools. Originality/value Schools can be visualized as guarded communities for creating a secure environment for students in support of learning. This research study shows that the combined cognitive capital, structural capital and relational capital mediate the impacts of total quality leadership on innovativeness in schools. Thus, school leaders should first establish a mechanism to develop social capital among their employees to bring up innovative initiatives.
Keywords: Organizational innovativeness; School leaders; Social capital; TALIS; Total quality leadership; dept.mgt; peer-reviewed

Green supply chain management: A theoretical framework and research directions - Birasnav, M.; Chaudhary, Richa; Henry Dunne, James; Bienstock, Joshua; Seaman, Cristina (Computers & Industrial Engineering, 2022)
Practitioners and academicians dedicate significant attention to tackling initiatives and executing mechanisms to address society’s environmental concerns. Further, organizations and researchers recognize that there is a need to implement green supply chain management (GSCM) practices as a part of green strategy. To date, embedding a sustainability dimension into supply chain management remains a challenge for organizations given the lack of systematic knowledge of the key dimensions of GSCM practices, the factors that influence the implementation of GSCM practices, and the benefits that organizations gain through the implementation of such practices. To address this problem, this study reviews 151 research articles published between 1997 and 2021 in the GSCM literature, and offers a theoretical framework that synthesizes and integrates the knowledge acquired from the reviewed literature. This framework includes various dimensions of GSCM practices identified in the past research studies, the antecedents that influence implementation of GSCM practices, and the outcomes of implementation of such practices. Further, this study offers theoretical and practical perspectives to support future research utilizing a research model as a baseline to guide organizations in the understanding of the primary GSCM attributes, their predictors, and benefits.
Keywords: Antecedents; Green supply chain; Outcomes; Systematic literature review; dept.mgt; peer-reviewed